The Relationship of Balance, Agility, and Speed to Dribbling Ability in a Football Games - Hakim, Hikmad; Amahoru, Nurul Musfira; Saleh, Taufiqurrahman (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to find out: the relationship of balance, agility, and speed to the ability to grit the ball in a football game. This study belongs to the type of correlation research. The population of this study was all students of Madrasah Aliyah DDI Pattojo, Soppeng Regency class X and XI with a total research sample of 30 students selected by random sampling. The data analysis techniques used are descriptive, data normality, correlation, and regression using the SPSS system Version 21.00 at a significant level of 95% or a0.05. Based on the results of data analysis, this study concluded that: (1) Balance has a significant relationship with the ability to grasp the ball in football games obtained a correlation value (r) -0.855 with a probability level (0.000) <a0.05;( 2) Agility has a significant relationship with the ability to grit the ball in a football game obtained a correlation value (r) 0.792 with a probability level (0.000) <a0.05;( 3) Speed has a significant relationship with the ability to grit the ball in a football game, obtained a correlation value (r) 0.720 with a probability level (0.000) <0.05; and (a4) Balance, agility and speed have a significant relationship with the ability to grin the ball in a football game, obtained regression value (R) 0.923 with a probability level (0.000) <0.05a.